Where in the world - French, Simon, 1957- (Australia : Little Hare Books, 2008)
Ari, leaving his home in Germany for a new life and family with his mother in Australia, is forced to part from the grandfather who taught him to play the violin, but he finds that his music and memories are intertwined.
5.5
5-8
Keywords: Grandfathers -- Juvenile fiction; Memory -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Musicians -- Juvenile fiction; Violin -- Juvenile fiction; Grandfathers -- Fiction; Memory -- Fiction; Mothers and sons -- Fiction; Musicians -- Fiction; Violin -- Fiction; Mother-son relationship -- Fiction; Violins -- Fiction; Australia -- Juvenile fiction; Australia -- Fiction